Fatal Complications after Pediatric Surgical Interventions: Lessons Learned - Willemijn M. Klein; Mayke E. Van der Putten; Benno Kusters; Bas H. Verhoeven (Georg Thieme Verlag KG, 2017)
Placement of catheters, drains, shunts, and tubes in children can lead to serious or even fatal complications at the moment of placement, such as hemorrhage at insertion, or in the longterm, such as infections and migration into adjacent organs. The clinician should always be aware of these potential complications, especially if the child is unwell. For postmortem diagnostic evaluation, either with a computed tomography scan or an invasive autopsy, all tubes, drains, shunts, and/or catheters should be left in situ. We present three cases with fatal complications after the placement of a chest drain, ventriculoperitoneal shunt, and gastrostomy tube.